Mood state at the beginning of the pregnancy and its influence on obstetric and perinatal outcomes - Ernesto S. González-Mesa; M. Luisa Arroyo-González; Nadia Ibrahim-Díez; Olga Cazorla-Granados (Taylor & Francis Group, 2019)
Aim: We designed this study to ascertain the prevalence of depressive disorders and anxiety at the beginning of the pregnancy, studying possible associated factors and assessing the influence of mood disorders on perinatal outcomes. Methods: A representative sample of 191 pregnant women at first trimester of their pregnancies completed a questionnaire that included the Whooley´s questions, the Spanish version of the Beck Depression Inventory (BDI), the State-Trait Anxiety Inventory and a series of questions related to health status, general mood and sociodemographic variables. Later, we prospectively evaluated the influence of anxiety and depression on the perinatal and obstetric results in 145 of them. Results: More than 20% of pregnant women presented high levels of anxiety. The mean values of the state and trait anxiety scores were 38.7 (SD 9.8) and 34.5 (SD 9.5). The mean BDI score was 5.97 (SD 4.9), with 9.5% of participants achieving scores compatible with depression, (61% mild in, 22.2% moderate, and 16.6% severe). BDI scores were significantly lower in women who became pregnant after assisted reproductive techniques. We observed an association between depression and trait anxiety scores with an infant's low birth weight. The multivariate analysis showed that the feeling of happiness at the beginning of pregnancy was the best predictor of foetal weight. Conclusion: The prevalence of emotional disorders in the first trimester of pregnancy is high, with more than 20% of pregnant women presenting high levels of anxiety, and more than 9.5% presenting depression. During the first trimester, depression and anxiety were associated with low birth weight.